In Silico Prediction of Preventive Activities of Bioactive Hazelnut Peptides Against COVID-19 and Monkeypox 2022 - Güneş, Zeynep Saliha; Çakır, Bilal; İbrahim; Sönmez, Zeynep Saliha Güneş; Çakır, Bilal (John Wiley and Sons Inc, 2024)
The coronavirus 2 (SARS-CoV-2), a positive-sense RNA virus that causes severe acute respiratory illness, is the cause of Coronavirus Disease 2019 (COVID-19) and Monkeypox is a zoonotic viral disease caused by a double-strand enveloped DNA virus, a member of the Poxviridae family under the umbrella of the Orthopoxvirus genus. These viruses have harmed global health, societal stability, and global economy prompting the development of new therapeutic options. The purpose of this study was to analyze the potency of hazelnut-derived bioactive peptides for usage in preventive measures against SARS-CoV-2 and Monkeypox infections. Since SARS-CoV-2 entry into the host cell takes place through angiotensin-converting enzyme (ACE) receptors, an in silico attempt was made here to analyze the previously characterized ACE-inhibitory hazelnut peptides for their anti-COVID potential. First of all, peptide sequences with PeptideRanker values >0.5 were determined, where 43 of 256 hazelnut peptides met this condition. BIOPEP tools were used to calculate their ACE-inhibitory characteristics. VPHW and DENPRHF demonstrated the strongest ACE-inhibitory activity based on BIOPEP analysis. The binding potentials of VPHW (p < 0.001) and DENPRHF (p < 0.001) peptides to ACE were statistically significant based on PepSite2 analysis. The hazelnut-derived peptides were docked with ACE, spike proteins, SARS-CoV-2 proteases, host cell receptors, and Monkeypox 2022 membrane proteins using HPEPDOCK and CABS-dock. The in silico findings pointed out potential inhibition of SARS-CoV-2 main protease in the host cell and Monkeypox 2022 membrane protein and demonstration of multiple bioactivities.
Keywords: Bioactive peptides; COVID-19; Hazelnut protein hydrolysates; In silico analysis; Molecular docking; Monkeypox